2021
DOI: 10.18240/ijo.2021.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Changes of matrix metalloproteinases in the stroma after corneal cross-linking in rabbits

Abstract: AIM: To observe changes in the content of matrix metalloproteinases (MMPs) in the corneal stroma after corneal cross-linking (CXL) in rabbits, and further explore the corneal pathophysiological process after CXL. METHODS: Forty-two rabbits (42 eyes) were randomly divided into seven groups. One group served as the control group, while the other six groups were treated with CXL. The concentrations of MMPs in corneal stroma were evaluated through parallel reaction monitoring at baseline and 3, 7, 15, 30, 90, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…23 Changes in some enzyme levels cause collagen disorder. 24 Matrix metalloproteinases are thought to be responsible for stromal degradation in keratoconus, 25 which also affects collagen. Some publications have suggested that this collagen disorder is associated with premature death.…”
Section: Discussionmentioning
confidence: 99%
“…23 Changes in some enzyme levels cause collagen disorder. 24 Matrix metalloproteinases are thought to be responsible for stromal degradation in keratoconus, 25 which also affects collagen. Some publications have suggested that this collagen disorder is associated with premature death.…”
Section: Discussionmentioning
confidence: 99%
“…This is a surgical procedure associated with significant postoperative pain, 81 rare but potentially sight-threatening complications, 82 and a substantial cost ($US2000–$US4000/eye). 83 Of note, CXL cannot reduce MMP9 and TIMP expression 70 , 84 , 85 or stabilize corneal thickness. 64 , 86 88 Instead, Vit D supplementation significantly reduced the MMP-9/TIMP-1 ratio and collagen catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Increased availability and function of Vit D result in reduced MMP-9 levels and augmented TIMP-1 expression systemically. Consequently, collagen catabolism is inhibited, as shown by the decreased MMP-9/TIMP-1 ratio 69 , 70 and reduced serum concentration of collagen degradation products. Our data also suggest that inflammation can have a role in the process because MMPs are upregulated by many inflammatory cytokines, which are increased in the blood and the tear fluid in KC patients.…”
Section: Discussionmentioning
confidence: 99%